Mechanical and biodegradation properties of bamboo fiber‐reinforced starch/polypropylene biodegradable composites. Issue 20 (15th November 2019) - Yang, Feiwen; Long, Haibo; Xie, Baojun; Zhou, Wuyi; Luo, Ying; Zhang, Chaoqun; Dong, Xianming
ABSTRACT: Bamboo fiber (BF)‐reinforced starch/polypropylene (PP) composites were prepared by extrusion and injection molding methods. The mechanical and thermal properties and water absorption were evaluated by different methods. Moreover, composite samples were subjected to biodegradation through soil burial test and microbes medium degradation. Different stages of biodegradation were investigated by weight loss, attenuated total reflection Fourier transformed infrared spectroscopy, differential scanning calorimeter, and scanning electron microscope. It was found that contents of BF and starch resin had a significant influence on the properties of the composites. With more content of BF, the composite exhibited a better flexural property and biodegradation. A distinct decrease of weight loss and mechanical properties indicated the degradation caused by the microbes. After biodegradation, thermal stability of the composites decreased while the crystallinity of PP increased. The results prove that the composites more easily tend to be degraded and assimilated by microbes. © 2019 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2019, 137, 48694. Abstract : Elongation at break of the composite films after microbial degradation.